Digital Participation at the Margins: Online Circuits of Rap Music by Portuguese Afro-Descendant Youth. (February 2014) - Campos, Ricardo; Simões, José Alberto
In this article we examine how the internet and other digital technologies are used by Portuguese Afro-descendant youth living in contexts of socio-economic deprivation. More specifically, based on a set of interviews held with rappers, we pursue a discussion on the significance of the concepts of digital inclusion and participation, arguing that young people's online practices reflect not only distinct ways of digital participation but also cultural engagement. By studying black amateur rap, our main goal is to examine how disadvantaged young people use the internet and other digital technologies and how these apparatuses may be employed for cultural expression and identity construction. Our research shows, on the one hand, how crucial a strategic use of these devices can be for amateur cultural production, on the other hand, how these platforms contribute to build an enlarged circuit of ethicized cultural expression. Therefore, we argue that digital participation contributes to reverse the cultural devaluation experienced by these black communities, working as a mechanism of individual and cultural empowerment.